KATEKIS SEBAGAI MISIONARIS SEJATI - Dominikus I Gusti Bagus Kusumawanta (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Catechists are all Christ’s faithful, both clergy and laity, who are called and sent by God to be a preacher of the Word of God. In other words, the profession life of a catechist is to teach, preach the Word of God. Church limit that called catechists are lay people, both men and women, who were given a course of religion or those who follow the Catholic Religion Education. In the midst of the laity itself, a catechist is an integral part with the other lay. Proclamation in the governance of the world carried out jointly. In special tasks, this is where catechist becomes the herald of the Church. Just like the Saints who proclaim the life of Jesus Christ in their lives, catechist also proclaims the life of Jesus Christ in his life. That means that the proclamation of catechists not only by speaking words, but also through all aspects of life. This catechist not only heralds the catechism, but he himself is the catechism.